Determining biological variation of serum parathyroid hormone in healthyadults - Ercan, Müjgan (Array, 2019)
Measurement of parathyroid hormone (PTH) is essential in the investigation and management of calcium metabolism disorders. Toassess the significance of any assay result when clinical decision making biological variation (BV) of the measurand must be taken into consideration. The aim of the present study is determining the BV parameters for serum PTH.Materials and methods: Blood samples were taken at weekly intervals from 20 healthy subjects for ten weeks in this prospective BV study. Serum “intact PTH” concentrations were measured with electrochemiluminescence method. Biological variation parameters were estimated using the approach proposed by Fraser.Results: The values of within-subject biological variation (CVI), between-subject biological variation (CVG), analytical variation (CVA), reference change value (RCV) and individuality index (II) for serum PTH were 21.1%, 24.9%, 3.8%, 59.4% and 0.8%, respectively. Within-subject biological variation and CVG were also determined according to gender separately; 18.5% and 24.0%; 26.2% and 18.6% for male and female, respectively. Calculated desirable precision and bias goals were <10.6% and <6.3%, respectively.Conclusion: This study may contribute to BV data on serum PTH as it includes a sufficient number of volunteers from both genders over an acceptable period of time. We do not recommend the usage of population-based reference intervals for serum PTH concentrations. Reference change value may be helpful for the evaluation of serial serum PTH results. Nonetheless, evaluation of data according to gender is necessary when setting analytical performance specifications.